Проектування та розробка програмної системи автоматизованого відстеження переміщень людей у приміщенях - Трофуненко, І. С. (ХНУРЕ, 2021)
In the modern world problem of tracking and identifying business employees and customers movement has became more actual with increasing number of daily business visitors and growing of the large companies staff. Companies offices and buildings continue expanding and the problem of movement tracking and access control becomes more urgent. To solve this issues companies are developing and using complex tracking systems, which can cost a lot of money. TrackMe is an advanced movement tracking and access control system, which can be used for the most type of businesses. It is modular system that is much integration easier and flexible than competitor`s systems.
Науковий керівник – доц. каф. ПІ Лещинський В. О.
Keywords: розробка програмної системи; відстеження переміщень людей